2011
DOI: 10.1136/archdischild.2011.300162.38
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between gravimetric measurement and visual estimation of postpartum blood loss

Abstract: Background In clinical practice, postpartum blood loss is usually estimated visually. Studies have demonstrated visual estimation of blood loss is inaccurate in comparison to other methods, but little attention has been given to gravimetric measurement (weighing). Objective To determine the difference between gravimetric measurement of blood loss (MBL) and visual estimation of blood loss (EBL) after delivery. Methods A prospective study recruited women in labour or having elective caesarean section. Blood-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Compared with visual estimation, gravimetric assessment of blood loss is more accurate in both simulated scenarios and real time studies. [24][25][26] Both volumetric and gravimetric are forms of quantitative measurement; studies have shown that when used in combination, the accuracy of blood loss assessment is improved. 27 Gravimetric blood loss assessment requires minimal resources and is a cost-effective method of assessing PPH.…”
Section: Methods Of Estimating or Measuring Blood Loss During Obstetr...mentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with visual estimation, gravimetric assessment of blood loss is more accurate in both simulated scenarios and real time studies. [24][25][26] Both volumetric and gravimetric are forms of quantitative measurement; studies have shown that when used in combination, the accuracy of blood loss assessment is improved. 27 Gravimetric blood loss assessment requires minimal resources and is a cost-effective method of assessing PPH.…”
Section: Methods Of Estimating or Measuring Blood Loss During Obstetr...mentioning
confidence: 99%
“…27 Gravimetric blood loss assessment requires minimal resources and is a cost-effective method of assessing PPH. 25 However, it can be labour intensive, requiring a designated member of staff trained in the process. The method also assumes that 1 g of blood is equal to 1 ml of blood, but as blood density is proportional to haematocrit, this value may be inaccurate in pregnancy and acute haemorrhage.…”
Section: Methods Of Estimating or Measuring Blood Loss During Obstetr...mentioning
confidence: 99%
See 2 more Smart Citations